The Utility of Mindfulness Training to Reduce Stress in South African Organisations - Szabo, Alexia Ursula (University of the Witwatersrand, Johannesburg, 2023)
Mindfulness training has become popular within organisations as a strategy to reduce stress amongst employees. The overarching aim of this study was to investigate whether mindfulness training should be considered in the South African workplace to assist in reducing perceived stress. The research was underpinned by the mindful coping model developed by Garland et al. (2009), developed from the Transactional Model of Stress and Coping (Lazarus & Folkman, 1984). A sample of 103 working South Africans responded to a self-reported questionnaire which measured their mindfulness levels (MAAS), and perceived levels of stress (PSS-10). In addition, the questionnaire assessed whether they have participated in mindfulness training and actively engage in a mindfulness practice. Correlational analyses showed a significant, inverse relationship between mindfulness levels and perceived stress. However, the research found no statistically significant difference between the mindfulness or perceived stress levels of employees who have participated in mindfulness training or who currently have a mindfulness practice. The theoretical and practical implications of these findings are discussed.
A research report submitted in partial fulfillment of the requirements for the degree of Master by coursework and research report in Organizational Psychology in the faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023
Keywords: Stress; mindfulness; Mindfulness training; South African organisations; South Africa; Employees.; UCTD; SDG-3: Good health and well-being